You Shook Me All Campaign Long Music in the 2016 Presidential Election and Beyond - Kasper, Eric T.; Schoening, Benjamin S. (University of North Texas Press, 2018)
Music has long played a role in American presidential campaigns as a mode of both expressing candidates' messages and criticizing the opposition. The 2016 campaign was no exception and was a game changer. The ten chapters in this collection place music use in 2016 in historical perspective before examining musical messaging, strategy, and parody. The book ultimately explores causality: how do music and musicians affect presidential elections, and how do politicians and campaigns affect music and musicians? The authors explain this interaction from various perspectives, with methodological approaches from several fields, including political science, legal studies, musicology, cultural studies, rhetorical studies, and communications and journalism."The cumulative effect of the authors' expertise on campaign music makes this book a tour-de-force."-Nancy S. Love, author of Musical Democracy